Evaluating The Role Of Public Health Infrastructure In Enhancing Health Security In Saudi Arabia (The Review of Diabetic Studies, 2024)
Health security has emerged as a critical priority for nations worldwide, particularly in the wake of global health emergencies, pandemics, and evolving epidemiological threats. Public health infrastructure plays a pivotal role in strengthening a country’s capacity to prevent, detect, and respond to health risks. Saudi Arabia, as a regional and global hub for religious tourism and international mobility, faces unique public health challenges that necessitate robust and resilient health systems. This study evaluates the role of public health infrastructure in enhancing health security in Saudi Arabia, focusing on healthcare facilities, disease surveillance systems, workforce capacity, emergency preparedness, digital health innovations, and governance frameworks. Using a qualitative and analytical approach, the study examines how investments in infrastructure have contributed to improved disease control, emergency response, and population health resilience. The findings indicate that Saudi Arabia’s strategic reforms, aligned with Vision 2030, have significantly strengthened public health preparedness and response capabilities. However, challenges remain in workforce distribution, intersectoral coordination, and addressing non-communicable disease burdens. The study concludes that sustained investment, integrated governance, and community engagement are essential to further enhance health security and ensure long-term public health resilience in Saudi Arabia.